The Effects of Output Interference, Availability, and Accounting Information on Investors' Predictive Judgments. - Moser, Donald V. (The Accounting Review, 1989)
Abstract ABSTRACT: Prediction 18 one of the most important aspects of investment decision making. This study provides evidence that investors' predictive earnings judgments can be systematically Influenced as a consequence of the combined effects of "output interference" and "availability," and that the use of financial accounting information in the prediction process seems to provide limited benefit in terms of reducing this effect. Output Interference Is a psychological concept that Implies that whatever is thought about first interferes with, and thus inhibits, later thoughts about an Issue. An availability-based prediction strategy is one in which the decision maker uses the relative number of pro versus con masons generated, and/or the ease with which such reasons can be generated, as cues in judging the likelihood of future events. Fifty-eight Investors participated in an experiment that demonstrated that the order in which they considered opposing arguments regarding the possibility of reaching a specified level of earnings had an impact on both their ability to generate supporting and opposing masons and their subsequent probability judgment that earnings would actually reach the specified level. The outcome for which the Investors were able to generate the most supporting masons was judged more probable, investors were able to think of more reasons supporting a particular outcome, not because there were more such reasons in the objective environment, but rather as a consequence of output interference. The systematic effect on judgment, although perhaps slightly reduced, persisted when investors had access to financial statements while considering the company's earnings prospects.